(untitled) (Raparin Journal of Humanities (RJH), 2020)
Seventeenth-century scholars have lately argued that if there was one thing to be revolutionized by the political disturbance in the early decades of the century, it was reading. The political instability caused by the battle between the king and the Parliament undeniably, and effectively influenced people’s lives, but people were also indirectly and intellectually experiencing those occurrences through reading about them (Anderson and Sauer 217). Jesse Lander also notes a ’’consequential intersection between religious controversy and print technology in early modern England’’ (1). Printed polemical exchange then becomes one of the most distinctive features of the era, as instantiated by the puritan Thomas Edwards’s 1646 Gangraena and the immediate responses it attracted. This paper investigates the publishing, and reading culture of seventeen century Britain by examining how the Independent John Goodwin-Edwards’s Cretensis responds to Gangraena, contextually analyzing some of the strategies he applies, while at the same time probing the immediate context. The report concludes with a brief account in which it is stated how the response in question helps illuminating the nature of polemical print controversy in early modern England.